Effective Factors on Alignment of Accounting Information Systems in Manufacturing Companies: Evidence from Iran - Hajiha, Zohreh (Information Management and Business Review, 2011)
This study examines accounting information systems (AIS) alignment and its effective factors in the context of manufacturing companies in industries of food and beverage, sugar, materials and pharmaceutical companies listed in Tehran Stock Exchange (TSE), in Iran. Strategic alignment is very important in increasing company’s performance, however, few studies have been made to investigate the factors that affect alignment and therefore, in this study we aimed to identify different levels of AIS alignment of Iranian companies and then investigated the factors that affect in this alignment. We defined AIS alignment as adoption between AIS requirements and AIS capacity. Using a questionnaire, data from 81 companies (include their financial and executive managers) were gathered on nineteen accounting information specifications for both requirements and capacity of AIS. We applied moderation view for fitness between these two items. Then cluster analysis was applied to categorize companies in two groups of aligned and unaligned. The study then investigated some factors that might be related to AIS alignment. Findings indicate that AIS alignment was related to level of managerâ€™s accounting and IT knowledge; usage of accounting and audit firms as external experts of AIS; and usage of internal IT staff. The company size is also related to AIS alignment. It is important for companies to consider these effective factors on their AIS alignment so that opportunities can be recognized to improve AIS alignment that support their information needs in competitive environment.